Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

The mycobiome of Cassiopea xamachana as determined by culture-based and metagenomic sequencing - Victoria Sharp; Marta Mammone; Charles Dye; Raúl A. González-Pech; Oded Yarden; Mónica Medina (Symbiosis, 2025)

Correction: Accelerating Elevation Gain Indicates Land Loss Associated with Erosion in Mississippi River Deltaic Plain Tidal Wetlands - Camille LaFosse Stagg; Leigh Anne Sharp; Emily Fromenthal; Brady Couvillion; Victoria Woltz; Sarai Piazza (Estuaries and Coasts, 2024)

Accelerating Elevation Gain Indicates Land Loss Associated with Erosion in Mississippi River Deltaic Plain Tidal Wetlands - Camille LaFosse Stagg; Leigh Anne Sharp; Emily Fromenthal; Brady Couvillion; Victoria Woltz; Sarai Piazza (Estuaries and Coasts, 2024)
In recent years, the Mississippi River Deltaic Plain (MRDP) has experienced the highest rates of wetland loss in the USA. Although the process of vertical drowning has been heavily studied in coastal wetlands, less is known about the relationship between elevation change and land loss in wetlands that are experiencing lateral erosion and the contribution of erosion to land loss in the MRDP. We quantified relationships of elevation change and land change in ten submerging tidal wetlands and found that, despite significant land loss, elevation trajectories in seven of the land loss study sites were positive. Furthermore, we observed an acceleration in elevation gain preceding the conversion from vegetated marsh to open water. To identify regional contributions of lateral erosion to land loss, we quantified the relationship of elevation change and land change in 159 tidal marsh sites in the MRDP. Approximately half the sites were persistently losing land, and 82% of these sites were vulnerable to erosion, identifying erosion as a dominant mechanism of coastal wetland loss in this region. Notably, the sites that were vulnerable to erosion were experiencing land loss while also gaining elevation, and sites with the highest land loss exhibited accelerating elevation gain. Together, these data illustrate that (1) erosion is a dominant mechanism of wetland loss in the MRDP, (2) accelerated elevation gain is an indicator of erosion, and (3) consideration of elevation change trajectories within the context of land change is critical for providing accurate coastal wetland vulnerability assessments.

The influence of photosymbiosis in Cassiopea xamachana regenerative success - Marta Mammone; Victoria Sharp; Michael Hewitt; Mónica Medina (Symbiosis, 2023)

Unique combinations of coral host and algal symbiont genotypes reflect intraspecific variation in heat stress responses among colonies of the reef-building coral, Montipora digitata - Javid Kavousi; Vianney Denis; Victoria Sharp; James Davis Reimer; Takashi Nakamura; John Everett Parkinson (Marine Biology, 2020)

Regulation of glucocorticoid metabolism in the boar testis and caput epididymidis by the gonadotrophin-cAMP signalling pathway - Victoria Cabrera-Sharp; Samantha M. Mirczuk; Elaine Shervill; Anthony E. Michael; Robert C. Fowkes (Cell and Tissue Research, 2013)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)